Review on the design, production and study of the intelligent smoke dryer - Sawalda Guidzavaï, Alphonse; Ngasop, Ndjiya; Njintang , Nicolas; Tchami, Hilaire; Brisco Ngnassi Djami , Aslain; Ngnassi Nguelcheu , Ulrich (International Journal of Engineering and Technology, 2023)
Smoking and drying are widely used techniques for preserving food to reduce losses and ensure availability of food in all seasons in developing countries where cost and high technology are out of reach. The effectiveness of ancestral know-how and techniques of these conservation methods being indisputable, it is desirable to improve practices due to the arduousness, health problems of processors and consumers, loss of materials and resources; the irregularity of the quality of the finished product and the loss of time are always perceived. Added to these disadvantages is the lack of information on the evolution of the transformation process which impacts the quality of the finished product. This review aims to take stock of the scientific bases of smoking and drying, the processes and equipment for preserving meat products as well as the laws on the marketing and consumption of these products. It emerges from this study that a device for smoking and drying meat products, and its process making it possible to guarantee food safety, user safety, retaining all nutrients, ergonomic, using fewer resources, fast, adaptable to any type and size of smoking products is not yet present in our markets.